Kedudukan Dan Akibat Hukum Akta Wasiat Yang Dibuat Oleh Suami Dihadapan Notaris Terkait Harta Bersama - Siregar, Inda (Jurnal Ilmiah Wahana Pendidikan, 2025)
The inner and outer bond between husband and wife to form a happy family. That bond is called marriage. In marriage there is mixing and separation of assets. There is no marriage agreement for joint property, while for separation of property there is a marriage agreement. If joint assets are willed, they cannot immediately be willed to another person or party because there are still assets of the spouse. A deed of will that has been made before a notary if someone is harmed. The position of a will is not absolute. For legal certainty and fairness, one of the spouses can sue the court for the division of joint assets or request the annulment of the Will Deed. Cancellation or adjustments to the contents of a will can occur in the judicial process to protect the rights of legal heirs, especially the wife as the legal owner of half of the joint assets. Notaries have a big responsibility to ensure the legal status of bequeathed assets. The notary ensures that the contents of the document are clear, unambiguous, and in accordance with the will of the testator. Identity and Capacity Verification: Before drafting the deed, the notary must verify the identity and legal capacity of the testator.